Women and Superannuation: Work Until You Drop? - Vu , Jo (Chau); Doughney , James (Journal of Law and Governance, 2009)
Superannuation is becoming an increasingly important source of retirement income. However, women in Australia face a significant barrier in accumulating superannuation entitlements because of their positions in the paid and unpaid workforce. When in paid work, women occupy lower positions, have more career breaks due to care responsibilities and have more part-time and casual employment. Many women, of course, do not work outside the home, and a smaller proportion of women engage in paid employment than do men. Consequently women have lower incomes, less wealth and less generous retirement benefits. Our analysis of the Survey of Employment Arrangements and Superannuation and other Australian Bureau of Statistics data, together with data published by the Australian Prudential Regulatory Authority, reveals that dramatic policy initiatives will be needed to improve women’s access to retirement resources. Such policies do not apply only to superannuation but must address women’s positions in the paid workforce and their care responsibilities.